Theories of finance and financial crisis: Lessons for the Great Recession - Nina Dodig; Hansjörg Herr (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2015)
This paper presents an overview of different models which explain financial crises, with the aim of understanding economic developments during and possibly after the Great Recession. In the first part approaches based on efficient markets and rational expectations hypotheses are analyzed, which however do not give any explanation for the occurrence of financial crises and thus cannot suggest any remedies for the present situation. A broad range of theoretical approaches analyzing financial crises from a medium term perspective is then discussed. Within this group we focused on the insights of Marx, Schumpeter, Wicksell, Hayek, Fisher, Keynes, Minsky, and Kindleberger. Subsequently the contributions of the Regulation School, the approach of Social Structures of Accumulation and Post-Keynesian approach, which focus on long-term developments and regime shifts in capitalist development, are presented. International approaches to finance and financial crises are integrated into the analyses. We address the issue of relevance of all these theories for the present crisis and draw some policy implications. The paper has the aim to find out to which extent the different approaches are able to explain the Great Recession, what visions they develop about future development of capitalism and to which extent these different approaches can be synthesized.
Keywords: B14; B15; B24; B25; E11; E12; E13; E32; 330; theories of crisis; Marxian; Institutional; Keynesian; capitalism; finance; financial crisis